2004
DOI: 10.1002/em.20041
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mutant frequency and mutation spectrum for gene A of ΦX174 grown in E. coli

Abstract: The use of transgenic targets for measuring mutant frequencies in mammalian tissue requires an estimate of the mutant frequency that results from recovery of the transgene in bacterial recovery systems. In this study, we have determined the spontaneous mutant frequency, estimated the mutation rate, and ascertained the mutation spectrum for gene A of phiX174 grown in E. coli strain CQ2 from 156 small independent cultures. The mutant frequency of 12 of the 156 cultures was 17 +/- 1.0 x 10(-6) and the estimated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…We used the Luria-Delbrück fluctuation test to infer viral mutation rates in the presence/absence of 5-FU based on the appearance of mutants capable of growing in a nonpermissive host strain (gro87). The WT showed an average spontaneous mutation rate of ϭ (0.86 Ϯ 0.10) ϫ 10 Ϫ6 s/n/r, consistent with previous work (32,34), and the V2A and D8A substitutions had no significant effect on this rate in the absence of 5-FU (P ϭ 0.399 by two-way ANOVA). In contrast, in cells treated with 5-FU, there were differences among the mutation rates of the WT, V2A, and D8A viruses (P ϭ 0.004).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We used the Luria-Delbrück fluctuation test to infer viral mutation rates in the presence/absence of 5-FU based on the appearance of mutants capable of growing in a nonpermissive host strain (gro87). The WT showed an average spontaneous mutation rate of ϭ (0.86 Ϯ 0.10) ϫ 10 Ϫ6 s/n/r, consistent with previous work (32,34), and the V2A and D8A substitutions had no significant effect on this rate in the absence of 5-FU (P ϭ 0.399 by two-way ANOVA). In contrast, in cells treated with 5-FU, there were differences among the mutation rates of the WT, V2A, and D8A viruses (P ϭ 0.004).…”
Section: Resultssupporting
confidence: 89%
“…Despite this, the mutation rates of the single-stranded DNA bacteriophages X174 and m13 are clearly distinct from those of their host, Escherichia coli, and are highest among DNAbased genomes, averaging 10 Ϫ6 s/n/r (32)(33)(34). Also, the fast molecular evolution of animal and plant single-stranded DNA viruses suggests that their mutation rates are elevated (6), although these have not been measured.…”
Section: Iral Mutation Rates Vary Amply From 10mentioning
confidence: 99%
“…The following cross-check of this estimate suggests this value is probably low, but not unreasonable. When this rate is divided by an estimate of the per-genome mutation rate of 1.0 3 10 À2 from the closely related fX174 virus (Raney et al 2004;Cuevas et al 2009), it suggests that $1 in every 2000 mutations is beneficial. However, we observed 9 beneficial transitions on the g2534t background and a simple markrecapture model (Miller et al 2005) estimates that 18 exist.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that recombination contributes to geminivirus diversity (48,60,71). However, unlike doublestranded DNA (dsDNA) viruses, there is also mounting evidence that ssDNA viruses are subject to high nucleotide mutation rates similar to the levels reported previously for RNA viruses (34,35,53). Thus, geminiviruses represent a unique opportunity to examine the processes that contribute to the genetic variation of ssDNA viruses as well as the mechanisms underlying virus evolution in plants.…”
mentioning
confidence: 99%
“…Studies of bacterial and animal systems indicated that the mutation rates of dsDNA and ssDNA viruses differ significantly. The mutation rates for dsDNA phages range from 10 Ϫ7 to 10 Ϫ8 , while ssDNA phages display rates of approximately 10 Ϫ6 (15,53). Like dsDNA phages, polyomavirus and papillomavirus genomes display low mutation rates (10 Ϫ8 to 10 Ϫ9 ), similarly to their hosts (26).…”
mentioning
confidence: 99%